(untitled) (Research in Agriculture Livestock and Fisheries, 2018)
A study was undertaken to determine the prevalence of poultry diseases as well as the efficacy of challenge vaccine [ND killed (Lasota)] against Newcastle disease (ND) in commercial broiler and layer farms of Chittagong Metropolitan Area (CMA) during the period from December 2016 to February, 2017. A total of 134 birds were examined from 52 commercial broiler farms and 15 layer farms (two from each farm). The diseases of 67 farms were diagnosed based on the history, clinical signs and post-mortem findings and the efficacy of the ND killed (Lasota) vaccine was determined on the basis of hemagglutination inhibition (HI) test before and after vaccination. Sixty blood samples (20 from each of 3 broiler farms) and 48 eggs (16 from each of 3 layer farms) were collected and HI tests were performed. Among the 67 farms, the prevalence of colibacillosis, salmonellosis, necrotic enteritis, Newcastle disease, infectious bursal disease, mycoplasmosis, brooder pneumonia and mixed infections of colibacillosis and coccidiosis were 11.94%, 4.48%, 7.46%, 8.95%, 16.42%, 7.46%, 5.95% and 7.46%, respectively. Due to vaccination with ND killed (Lasota) vaccine at initial stage of infection the mortality rate reduced to zero and HI titre of the broiler farms increased as 5.40 to 7.55, 4.6 to 7.25, 4.65 to 7.70 and in the layer farms as 4.56 to 7.13, 5.0 to 7.81, 4.93 to 8.13. Due to ND challenge vaccine the initial HI titre level significantly (p<0.05) varies from post HI titer level within both broiler and layer farms. Res. Agric., Livest. Fish.5(2): 201-208, August 2018